Some theoretical aspects of the concept «archetype» - Demessinova Л.М. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2020)
The article presents a comprehensive analysis of the concept of «archetype», as well as the conclusions of scientists in the field of psychoanalysis, philosophy and literature. Psychological research K.G. Jung and his followers, as well as the structural analysis of C. LevyStrauss, were analyzed. The term is scientifically interpreted by the concept of the collective unconscious. Theoretical ideas in the article were analyzed on the basis of literary works and myths in Kazakh literature. The revival of archetypal images and symbols, plots and motifs in modern Kazakh literature has been proved using examples from works.